Conceptual density functional theory under pressure: Part I. XP-PCM method applied to atoms. Issue 32 (3rd August 2022) - Eeckhoudt, J.; Bettens, T.; Geerlings, P.; Cammi, R.; Chen, B.; Alonso, M.; De Proft, F.
Abstract : Conceptual DFT has provided a framework in which to study chemical reactivity. Since high pressure is more and more a tool to control reactions and fine-tune chemical properties, this variable is introduced into the CDFT framework. Abstract : High pressure chemistry offers the chemical community a range of possibilities to control chemical reactivity, develop new materials and fine-tune chemical properties. Despite the large changes that extreme pressure brings to the table, the field has mainly been restricted to the effects of volume changes and thermodynamics with less attention devoted to electronic effects at the molecular scale. This paper combines the conceptual DFT framework for analyzing chemical reactivity with the XP-PCM method for simulating pressures in the GPa range. Starting from the new derivatives of the energy with respect to external pressure, an electronic atomic volume and an atomic compressibility are found, comparable to their enthalpy analogues, respectively. The corresponding radii correlate well with major known sets of this quantity. The ionization potential and electron affinity are both found to decrease with pressure using two different methods. For the electronegativity and chemical hardness, a decreasing and increasing trend is obtained, respectively, and an electronic volume-based argument is proposed to rationalize the observed periodic trends. The cube of the softness is found to correlate well with the polarizability, both decreasing under pressure, while the interpretation of the electrophilicity becomes ambiguous at extreme pressures. Regarding the electron density, the radial distribution function shows a clear concentration of the electron density towards the inner region of the atom and periodic trends can be found in the density using the Carbó quantum similarity index and the Kullback–Leibler information deficiency. Overall, the extension of the CDFT framework with pressure yields clear periodic patterns.